Studi literatur: Perbandingan pendidikan inklusif indonesia dan jepang - Julievida, Afifah Berlian; Alam, Abdal Malik Fajar (Maliki Interdisciplinary Journal, 2024)
Inclusive education is important education that must be implemented in every country. This education functions as an alternative for the advancement of a country in terms of its education, because inclusive education views every student as equally entitled to the education they receive. Each country has very fundamental differences in inclusive education. These differences include, among other things, the systems, policies and services provided. This article will discuss the comparison of the inclusive education systems of Indonesia and Japan. The method used for this comparison is literature study.